THE CORRELATION OF MOTHER’S KNOWLEDGE AND ATTITUDE WITH BREASTFEEDING PRACTICES IN TULANG BAWANG BARAT DISTRICT AT 2021 (Jurnal Mitra Kesehatan, 2021)
Introduction:Breast milk is a liquid formed from a mixture of two substances, namely fat and water contained in a solution of protein, lactose and inorganic salts produced by the mother's breast glands, and is useful as baby food. Mother's knowledge and attitude in exclusive breastfeeding plays an important role in increasing the growth and development of children. The purpose of this study was to determine the relationship between the level of knowledge (cognitive factors) and attitudes (affective factors) of mothers in the practice of exclusive breastfeeding in Tulang Bawang Barat District in 2021. Method: This research is a quantitative research, with a cross sectional approach. The population in this study were all mothers who had babies > 6 months-12 months as many as 2285 with samples taken as many as 93 respondents. The object of this research is exclusive breastfeeding, knowledge and attitude. The research was conducted in June 2021 in the District of Tulang Bawang Barat. Collecting data using a questionnaire, data analysis is univariate, bivariate and multivariate. Results: The results showed that there was a relationship between knowledge (p value = 0.016, OR = 3.264), and attitudes (p value = 0.001, OR = 7.848) towards exclusive breastfeeding in Tulang Bawang Barat District in 2021. Dominant factors related to exclusive breastfeeding in Tulang Bawang Barat District in 2021, namely the attitude with a p-value of 0.000 OR 10.197. Conclusion: The dominant factor related to the practice of exclusive breastfeeding in Tulang Bawang Barat is the attitude of the mother. To improve the attitude of mothers in the Practice of Exclusive Breastfeeding, the Health Office needs to carry out health promotions with a more frequent frequency by using more attractive health promotion media in collaboration with the health promoter team at the puskesmas.